2014
DOI: 10.1159/000363226
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Covariates of Elevated Depressive Symptoms in Rural Memory Clinic Patients with Mild Cognitive Impairment or Dementia

Abstract: Background/Aims: To estimate the prevalence, severity, and covariates of depressive symptoms in rural memory clinic patients diagnosed with either mild cognitive impairment (MCI) or dementia. Methods: In a cross-sectional study of 216 rural individuals who attended an interdisciplinary memory clinic between March 2004 and July 2012, 51 patients were diagnosed with MCI and 165 with either dementia due to Alzheimer's disease (AD) or non-AD dementia. The Center for Epidemiologic Studies of Depression Scale (CES-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…Depression is a common comorbid disorder of dementia, affecting between 6% and 61% of PwD (Bielinski and Lawlor, 2006;Snowden et al, 2015). Evidence on factors associated in dementia suggests that dependency with daily activities (Starkstein et al, 2005;Knapskog et al, 2013), poor cognition (Kosteniuk et al, 2014), behavioral problems (Gruber-Baldini et al, 2005;Van der Mussele et al, 2013), poor QoL (Kosteniuk et al, 2014), and high levels of pain (Chou, 2007;Zwakhalen et al, 2009) have all been linked to depression. Further analysis using a multinational sample comprising eight European countries and reported at each of the three stages of dementia (mild, moderate, severe) could provide additional insights into the factors linked to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common comorbid disorder of dementia, affecting between 6% and 61% of PwD (Bielinski and Lawlor, 2006;Snowden et al, 2015). Evidence on factors associated in dementia suggests that dependency with daily activities (Starkstein et al, 2005;Knapskog et al, 2013), poor cognition (Kosteniuk et al, 2014), behavioral problems (Gruber-Baldini et al, 2005;Van der Mussele et al, 2013), poor QoL (Kosteniuk et al, 2014), and high levels of pain (Chou, 2007;Zwakhalen et al, 2009) have all been linked to depression. Further analysis using a multinational sample comprising eight European countries and reported at each of the three stages of dementia (mild, moderate, severe) could provide additional insights into the factors linked to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults are disproportionately affected by several chronic conditions. Among the elderly, chronic conditions such as cognitive impairment and depression are interrelated and often coexist [ 6 9 ], and at least one report confirms that each condition alone contributes to the increase of an older person's risk for mortality [ 10 ]. Recent studies have shown that subjects with MCI present more depressive symptoms compared with those without cognitive impairment [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the prevalence of depression was higher in memory clinic patients diagnosed with dementia due to AD compared to those diagnosed with MCI [ 5 ]. We previously observed that the prevalence of elevated depressive symptoms (depressive symptomatology) did not differ significantly between memory clinic patients with non-AD dementia versus those with AD dementia (38.2 vs. 27.3%); however, we found a significantly higher prevalence and severity of elevated depressive symptoms in patients with MCI than in those with dementia due to AD and non-AD dementia (51 vs. 23.9%) [ 15 ].…”
Section: Introductionmentioning
confidence: 76%